ADMITTING GUILT IN COURT CASE IN ACCORDANCE WITH NEW LEGISLATIVE CHANGES - SIMONA TACHE (Challenges of the Knowledge Society)
Entry into force of the law no.202/2010 regarding some measures to speed up the trial processes already raises some problems of interpretation especially concerning cases that are pending. Such a situation was inevitable since the transitional provisions could not cover all situations arising in practice, and the law mentioned abovecreate some completely new institutions in our criminal law. But I believe that for the new institution of admitting guilt in court case, would be required to adopt transitional rules necessary to eliminate the controverses that arise and will arise in practice. As any new institution, admitting guilt in court case willrequire a certain period of time untill crystallize an unitary practice field, even more because the text contains some vague expressions. Unfortunately, the courts have no benefit yet of a fast and efficient mechanism for unifying the jurisprudence, and this fact will probably affect also the solutions that will be taken by the courts in this matter.